The challenge of supporting and monitoring safe wastewater use in agriculture in LMIC - Drechsel, Pay; Bartram, J.; Qadir, M.; Medlicott, K. O. (Nature Portfolio, 2024)
Unsafe water reuse in the informal irrigation sector dominates in the Global South and requires more attention to protect food safety and public health. Promoting formal wastewater use in conjunction with (usually constrained) investment in treatment capacities is not sufficient in LMIC. New approaches and indicators are needed across the formal and informal reuse sectors to increase food safety and monitor progress on safe reuse. Current reuse guidelines need to be updated with greater attention to policy, regulations, investments, and behavior change for a higher implementation potential.